RELICT HUMID TROPICAL FOREST IN MEXICO PROMOTES DIFFERENTIATION IN BARRED WOODCREEPERS Dendrocolaptes (AVES: FURNARIIDAE) - Navarro-Sigüenza, Adolfo G.; Almazán-Núñez, R. Carlos; Sánchez-Ramos, L. Enrique; Rebón-Gallardo, M. Fanny; Arbeláez-Cortés, Enrique (Zootaxa, 2020)
Humid tropical forests in Mesoamerica are distributed along the Atlantic slope and, in scattered locations, along the Mexican Pacific slope. These poorly explored Mexican forests include microendemic bird species. Two species in the genus Dendrocolaptes occur in lowland and foothill humid tropical forests of Mesoamerica. One of these, D. sanctithomae, is comprised of four subspecies, of which the two that occur in Mexico, D. s. sanctithomae and D. s. sheffleri, are distinctly different morphologically, and the latter is a poorly known microendemic taxon of the Mexican Pacific humid tropical forest in the Sierra Madre del Sur. We used both nuclear (nDNA) and mitochondrial DNA (mtDNA) to evaluate the genetic variation of D. sanctithomae in Mexico, and complemented this with a quantitative analysis of phenotypic traits. We also conducted analyses of environmental niche models to test the hypothesis of niche differentiation of D. s. sheffleri from other taxa of D. sanctithomae. Our phylogenetic reconstructions of mtDNA consistently recovered D. s. sheffleri and D. s. sanctithomae as reciprocally monophyletic, while they shared alleles of nDNA. These mtDNA differences are comparable with differences reported between other Dendrocolaptes sister-taxa pairs. Our analysis of phenotypic traits also indicated that the taxa differ in measurements of hallux and feather barring. In contrast, niche differentiation tests suggest that the niches of both taxa are more similar than expected by chance. Our evidence leads us to propose species status for D. sheffleri. This is an additional example of recent speciation in Mexico that indicates active and peripatric evolutionary differentiation in the northern Neotropics.